2005
DOI: 10.1001/archotol.131.5.413
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the LigaSure Vessel Sealing System During Superficial Lobectomy of the Parotid Gland

Abstract: To evaluate the usefulness of the LigaSure Precise instrument in superficial lobectomy of the parotid gland. Design: Prospective study of the surgical procedures in the LigaSure Vessel Sealing System and comparison with a conventionally treated control group. Setting: Secondary care academic referral center. Patients: Thirty-five patients with a parotid gland benign tumor were randomly allocated to 2 superficial lobe parotidectomy groups: 17 using the LigaSure procedure (group A) and 18 using the conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 8 publications
6
37
1
1
Order By: Relevance
“…It was considered that because bigger and deeper lobes of parotid gland tumour were included in the LigaSure TM Small Jaw group, therefore excessive blood loss was experienced in these cases compared with the traditional method cases. On the other hand, less bleeding has been reported when using LigaSurePrecise TM than the traditional methods, especially in patient who are at risk of haemorrhage (Prokopakis et al, 2005;Colella et al, 2005). The United States FDA (US Food and Drug Administration) authorizes LigaSure TM for cutting blood vessels and lymphatic vessels up to 7mm in diameter, and the resisting pressure is reported to be three times or more than usual arterial pressure (Kennedy et al, 1998;Heniford et al, 2001;Harold et al, 2003;Dubuc-Lissoir, 2003).Therefore, it was suggested that less bleeding was accomplished.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was considered that because bigger and deeper lobes of parotid gland tumour were included in the LigaSure TM Small Jaw group, therefore excessive blood loss was experienced in these cases compared with the traditional method cases. On the other hand, less bleeding has been reported when using LigaSurePrecise TM than the traditional methods, especially in patient who are at risk of haemorrhage (Prokopakis et al, 2005;Colella et al, 2005). The United States FDA (US Food and Drug Administration) authorizes LigaSure TM for cutting blood vessels and lymphatic vessels up to 7mm in diameter, and the resisting pressure is reported to be three times or more than usual arterial pressure (Kennedy et al, 1998;Heniford et al, 2001;Harold et al, 2003;Dubuc-Lissoir, 2003).Therefore, it was suggested that less bleeding was accomplished.…”
Section: Resultsmentioning
confidence: 99%
“…Preservation of the facial nerve was thought to be possible, if there was a distance of 1mm or more between the cutting edge and the facial nerve. It was reported that facial palsy was also a rare complication after parotid gland surgery using LigaSurePrecise TM (Prokopakis et al, 2005;Colella et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bazı cerrahlar sinir diseksiyonu ve kanama kontrolü için klemp kullanmayı, bazıları ise diseksiyonu hızlandırmak için hemostaz amacıyla ultrasonik bı-çak, monopolar ve bipolar koagülasyon da dahil çeşit-li yöntemler kullanmayı tercih ederler. [11] Parotis cerrahisinde kanayan damarları koagüle ederek dokuları ayıran monopolar elektrokoterin kullanımı fasyal sinirde termal veya elektriksel yaralanma yaparak ameliyat sonrası dönemde sinir fonksiyonlarında zayıflığa yol açabilir. [12] Kanamayı çabuk ve etkili bir şekilde durdurmak cerrahinin başarısını arttırır.…”
Section: Renkli şEkiller Derginin Online Sayısında Görülebilir (Wwwkunclassified
“…A harmonic scalpel uses ultrasound technology to denature proteins in vessel walls and tissues. Harmonic scalpel is able to seal vessels up to 5 mm in diameter, whereas bipolar electrosurgical devices only seal vessels reliably up to 2 mm in diameter [10,11]. It can be used for ligation, dissection and cutting.…”
Section: Introductionmentioning
confidence: 99%